2009
DOI: 10.1089/ees.2008.0389
|View full text |Cite
|
Sign up to set email alerts
|

Stable Partial Nitrification in an Up-Flow Fixed-Bed Bioreactor Under an Oxygen-Limiting Environment

Abstract: Stable partial nitrification followed by a denitrification or anammox process is a cost-effective alternative to conventional biological nitrogen removal processes, especially for wastewaters having a low carbon-to nitrogen (C=N) ratio. This article addresses partial nitrification in an up-flow fixed-film bioreactor operated for more than 265 days using low C=N synthetic wastewater. The study was carried out in the absence of external aeration, for further cutting down the cost of treatment. By controlling inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The experiments were conducted with simulated wastewater as per our previous study [6] and no organic carbon was added. Ammonia was added as (NH 4 ) 2 SO 4 in the required concentration for feed preparation (Fig.…”
Section: Synthetic Wastewatermentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments were conducted with simulated wastewater as per our previous study [6] and no organic carbon was added. Ammonia was added as (NH 4 ) 2 SO 4 in the required concentration for feed preparation (Fig.…”
Section: Synthetic Wastewatermentioning
confidence: 99%
“…The seed biomass was obtained from mixing biomass from two lab-scale reactors, one from an oxygen-limited, ammonia-oxidizing fixed film reactor [6] and another from a laboratory-scale ANAMMOX reactor treating ammonia under anaerobic conditions for more than 300 days (Bagchi et al, personal communication). The AOB and NOB populations in the fixed film bioreactor were confirmed through fluorescence in situ hybridization (FISH) assay using 5 0 fluorescein tagged Nsm 156 and Nit 3 probes.…”
Section: Seed Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…DO in the bioreactor and in the effluent was always below detectable limits, indicating the consumption of residual DO. Although DO loading of 0.05 mg O/(mg N day) in the bioreactor was negligible as compared to the NLR, our previous experiments showed that aerobic nitrifying bacteria have the ability to survive under such a limiting DO environment [28]. To decrease the NOB activity, a strategy bioreactor.…”
Section: Maintenance Of Anammox Activitymentioning
confidence: 99%
“…nitrite and oxygen. Although AOB also requires oxygen as substrate, studies have revealed that many AOB species are able to adapt their metabolism even in acute absence of oxygen [28,29].…”
Section: Maintenance Of Anammox Activitymentioning
confidence: 99%